Evaluasi Pembelajaran Berbicara di Kelas Tinggi - Armilah Armilah; Nadia Syahfitri; Novia Rahmadani Harahap; Juni Sahla Nasution (Badan Penerbit STIEPARI Press, 2024)
Speaking skills are a person's skills in communicating to other people verbally. Speaking skills are a form of human behavior that is related to neurological, linguistic and psychological factors. Speaking skills are a person's communication process in arranging various words into a sentence so that other people understand the message conveyed in the form of ideas, opinions, or in the form of expressing all feelings and contents of the heart. The main goal of speaking is to be verbally skilled in expressing ideas correctly, precisely and with reason, but without too much hesitation. In order to convey thoughts effectively, the speaker should understand the meaning of everything he wants to communicate, he must be able to evaluate the effect of his communication on his listener(s), and he must know the principles underlying all speaking situations, both in general and individually. This research uses the library research method, which is a way to collect data by understanding and studying theories from various literature related to the research topic. Data collected through searching and construction from various sources, such as books, journals and previous research. Library materials obtained from various references are analyzed critically and in depth to support research propositions and ideas.